The determination of the biological function of bacterial pink pigment and Fusarium chlamydosporum on alfalfa (Medicago sativa L.) - Huang, Rong; Zhang, Hong; Chen, Haiyan; He, Linxin; Liu, Xiaoni; Zhang, Zhenfen (Frontiers in Microbiology, 2023)
Bacterial pigment is one of the secondary metabolites produced by bacteria and has functions that are yet to be understood in relation to soil-borne pathogenic fungi and plants in mutualistic processes. The study evaluates the growth, photosynthetic, and physiological characteristics of alfalfa after interacting with different concentrations of Cp2 pink pigment and Fusarium chlamydosporum. The findings showed that Cp2 pink pigment has the ability to inhibit the growth of alfalfa, with the inhibition ratio gradually increasing with rising concentration. F. chlamydosporum inhibited the growth of alfalfa, which reduced the photosynthetic physiological response and elevated antioxidant enzymes, which are typically manifested by yellowing leaves and shortened roots. Under the combined effect of Cp2 pink pigment and F. chlamydosporum, increasing concentrations of Cp2 pink pigment intensified the symptoms in alfalfa and led to more pronounced growth and physiological response. This indicates that the Cp2 pink pigment is one of the potential virulence factors secreted by the Erwinia persicina strain Cp2, which plays an inhibitory role in the interactions between F. chlamydosporum and alfalfa, and also has the potential to be developed into a plant immunomodulator agent.